The Digital Economy Boom: How E-Commerce is Reshaping Indonesia’s Market - Jannah, Miftahul; Mahmuda, Zuhairo; Alankrita, Amla (Universitas Negeri Semarang, 2025)
This study examines the rapid growth of e-commerce and its transformative effects on Indonesia’s digital economy. As one of Southeast Asia's largest and most dynamic markets, Indonesia is undergoing a digital transformation that significantly alters traditional business models and consumer behavior. The research explores the role of e-commerce platforms in reshaping market structures, influencing business practices, and changing consumer purchasing patterns. Findings indicate that e-commerce is a key driver of economic growth, expanding access to goods and services across both urban and rural regions, and promoting financial inclusion. The study also highlights the crucial role of mobile technology and increased internet penetration in facilitating the widespread adoption of online shopping. However, challenges such as logistical inefficiencies, digital payment security, and regulatory frameworks pose significant barriers to the long-term sustainability of e-commerce in Indonesia. The novelty of this research lies in its comprehensive analysis of the digital economy’s evolution, with a specific focus on e-commerce as a central driver of economic change. Given the growing importance of the digital economy in Indonesia’s development, this research is vital for understanding the future trajectory of the market. The study offers valuable insights for businesses, policymakers, and stakeholders, providing recommendations for fostering a secure, inclusive, and sustainable e-commerce ecosystem in Indonesia.